Silver-Catalyzed [3+3] Annulation of Glycine Imino Esters with Seyferth–Gilbert Reagent To Access Tetrahydro-1,2,4-triazinecarboxylate Esters - Huang, Yin-Jun; Nie, Jing; Cheung, Chi Wai; Ma, Jun-An (Synlett, 2020)
A silver-catalyzed protocol for [3+3] annulation of glycine imino esters with Seyferth–Gilbert reagent was developed. A variety of phosphorylated tetrahydro-1,2,4-triazinecarboxylate esters were synthesized in moderate to good yields and with excellent diastereoselectivities. The dehydrogenation of a tetrahydro-1,2,4-triazine product to the corresponding triazine counterpart was also demonstrated.
Keywords: [3+3] annulation; glycine imino esters; Seyferth–Gilbert reagent; triazines; phosphorylation